2012
DOI: 10.1166/msr.2012.1003
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Ca<SUP>2</SUP><SUP>+</SUP> Signalling by NAADP: Two-Pore Channels in a Complex?

Abstract: NAADP is a potent Ca2+ mobilizing messenger in a variety of cells but its molecular mechanism of action is incompletely understood. Accumulating evidence indicates that the poorly characterized two-pore channels (TPCs) in animals are NAADP sensitive Ca2+-permeable channels. TPCs localize to the endo-lysosomal system but are functionally coupled to the better characterized endoplasmic reticulum Ca2+ channels to generate physiologically relevant complex Ca2+ signals. Whether TPCs directly bind NAADP is not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 139 publications
(241 reference statements)
3
24
0
Order By: Relevance
“…Second, the magnitude of NAADP-induced Ca 2+ currents is significantly reduced when NAADP is infused at 50-100 M, which is fully consistent with the well known desensitization of mammalian NAADP receptors in the high micromolar range [9]. Third, the Ca 2+ response to NAADP is abrogated by Ned-19, which selectively antagonizes NAADP binding to its receptor site [9,63]. Thus, NAADP triggers the activation of Ca 2+ -dependent currents in HeLa cells, thereby rendering these cells a suitable model to investigate the underlying Ca 2+ stores.…”
Section: Discussionsupporting
confidence: 78%
“…Second, the magnitude of NAADP-induced Ca 2+ currents is significantly reduced when NAADP is infused at 50-100 M, which is fully consistent with the well known desensitization of mammalian NAADP receptors in the high micromolar range [9]. Third, the Ca 2+ response to NAADP is abrogated by Ned-19, which selectively antagonizes NAADP binding to its receptor site [9,63]. Thus, NAADP triggers the activation of Ca 2+ -dependent currents in HeLa cells, thereby rendering these cells a suitable model to investigate the underlying Ca 2+ stores.…”
Section: Discussionsupporting
confidence: 78%
“…As such, a lower number of higher confidence candidates are identified relative to affinity purification methods and this is a key advantage. In contrast, whereas the longer list of candidates from affinity purification approaches (including TAP-tagging) must be more carefully validated to exclude false positives, casting a broader net may be critical for capturing dynamic, transient interactions that are potentially important for TPC activation [41,42,56]. Grimm et al [53] identified 26 TPC2 interactors from (HEK) human embryonic kidney cells transfected with mouse GFP–TPC2.…”
Section: Regulation Of Tpcs: a Proteomic Viewmentioning
confidence: 99%
“…As expression of the Ca v β var subunit unusually decreased Ca v current amplitude, displacement of Ca v β var from Ca v α complexes at the cell surface would be expected to relieve this inhibition thereby increasing Ca 2+ entry into schistosomes if replicated in situ . This proposal is not in itself unreasonable: several drugs are known to target accessory subunits/modulators of ion channels (discussed in [65]), and the approach of targeting protein-protein interaction interfaces is receiving increasing attention as a therapeutic strategy. Existing examples provide precedent for targeting Ca v channels [6668].…”
Section: The Effects Of Praziquantel On Ca2+ Signaling In Parasitimentioning
confidence: 99%